2019
DOI: 10.1021/acsmacrolett.9b00010
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Acetoacetyl Chemistry to Build Malleable Cross-Linked Polymer Networks via Transamidation

Abstract: Covalent adaptable networks (CANs) have various potential applications for their dynamic features benefiting from the existence of dynamic covalent bonds (DCBs). Here we exploit acetoacetyl chemistry to design CANs in which acetoacetyl formed amides (AFAs) act as a type of DCBs. We first illuminate that the transamidation of AFAs is ascribed to a "proton-switch" mechanism via model study and DFT calculations. When such AFA linkages are incorporated into cross-linked polymer networks, the malleability and recyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 33 publications
(40 reference statements)
5
46
0
Order By: Relevance
“…[1][2][3][4] Vegetable oils, as renewable resources, have unique chemical structures containing hydroxyls, esters, unsaturated sites, and other functional groups, and these can be modied to make low molecular weight polymeric materials for a range of versatile applications. [5][6][7][8][9] Acetoacetyl chemistry is interesting to use to prepare thermoset resins because acetoacetate functional groups can react with various groups, [10][11][12][13] including aldehydes, 14 isocyanates, 15 acrylates, 16 and amines. 17 Although many thermoset resins have been prepared using acetoacetate chemistry and amines, only a few studies have been reported on the synthesis of biobased coating materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Vegetable oils, as renewable resources, have unique chemical structures containing hydroxyls, esters, unsaturated sites, and other functional groups, and these can be modied to make low molecular weight polymeric materials for a range of versatile applications. [5][6][7][8][9] Acetoacetyl chemistry is interesting to use to prepare thermoset resins because acetoacetate functional groups can react with various groups, [10][11][12][13] including aldehydes, 14 isocyanates, 15 acrylates, 16 and amines. 17 Although many thermoset resins have been prepared using acetoacetate chemistry and amines, only a few studies have been reported on the synthesis of biobased coating materials.…”
Section: Introductionmentioning
confidence: 99%
“…Stress relaxation was characterized to investigate the effect of introducing DAM/PEEL on the formation of chemical and physical cross‐linking in PSA/DAM‐PEEL dual cross‐linking networks. The relaxation time, the recovery time of the materials, can be evaluated under constant strain conditions at the tested temperature, which is defined as the time required to relax to 1/e of the normalized stress relaxation modulus 48–50 …”
Section: Resultsmentioning
confidence: 99%
“…The relaxation time, the recovery time of the materials, can be evaluated under constant strain conditions at the tested temperature, which is defined as the time required to relax to 1/e of the normalized stress relaxation modulus. [48][49][50] Figure 3 is an illustration of the stress relaxation modulus (G r ) and normalized stress relaxation modulus of PSA/DAM-PEEL dual cross-linking networks at different PEEL contents. As illustrated in Figure 3(A), G r increased remarkably with the introduction of DAM/PEEL for all the samples.…”
Section: Rheological Properties Of Psa/ Dam-peel Dual Cross-linkingmentioning
confidence: 99%
“…We further explored whether the relaxation time was reflected in the chain mobility characteristics of the crosslinking network, which was evaluated as the time required to relax to 1/e of the normalized stress relaxation modulus. [34][35][36] Figure 5 shows the normalized stress relaxation of the acrylic PSAs as a function of time at 25°C. To evaluate chain mobility in the crosslinking networks, the normalized stress relaxation modulus of the acrylic PSAs was determined.…”
Section: Rheological Properties Of Acrylic Psasmentioning
confidence: 99%